"Devil's Lure Took All I Had": Moral Panic and the Discursive Construction of Crystal Methamphetamine in Australian News Media. (March 2019) - Fredrickson, Anne; Gibson, Alexandra Farren; Lancaster, Kari; Nathan, Sally
Crystal methamphetamine ("ice") has been a fixture in Australian newspapers since the early 2000s. This study explores discourses at work in constructing the ice "problem" in recent Australian media, possible implications for how people who use ice are discursively positioned, and the resulting significance for drug policy. Twenty-seven articles were selected for discourse analysis, sampled from a larger study of Australian ice-related news items. By critically engaging with sociological concepts of "moral panic" and the "risk society, " we demonstrate how three media discourses produce the subject of the "young person" as both victimized by ice and a catastrophic threat in and of themselves: (1) "ice traps and transforms youth, " (2) "ice does not discriminate, " and (3) "ice perverts sanctuary." These discourses illustrate the tensions between the meanings of ice use and understandings of safety and risk, speaking to current anxieties in Western, neoliberal societies. Ice use is further constructed as a form of abjection, threatening traditional social boundaries and institutions. However, the agency and determinism simultaneously granted to ice the substance troubles the notion we are witnessing yet another "drug scare" that polices social behavior. Instead, we observe how these discourses mirror those in the biomedical literature, which construct ice as a uniform, agentic, and uniquely dangerous drug. With use attributed to entrapment and/or naturalized as addiction, the drug is constituted as engineering its own, always harmful, consumption. This limits conceptions of any "safer, " "rational, " or "pleasurable" forms of ice use and further justifies state intervention on its users. Overall, these discourses rationalize prohibitionist interventions around ice and singularize drug consumption as a behavior requiring institutional management.